Interview with Jonas Löwgren - Rikke Ørngreen; Staffan Selander (Stockholm University Press, 2011)
Here we present an interview with Professor Jonas Löwgren, who is recognized for his work on both interaction design and communication design. We will present his interests and main questions, as well as his earlier work experiences, and how these have had an influence on his theoretical and practical research work today. One major question that Jonas puts forward is: Dissolution of the design object into a complex of communicative practices and services across media, pervading all aspects of everyday life, and the roles of interaction designers in this new landscape. With this interview, we would like to follow up these questions; to promote future dialogues between interaction and communication designers and people engaged in the design for - and in - learning communities.